Предмет: Математика, автор: dobrodomova

пожалуйста помогите.

Приложения:

Ответы

Автор ответа: tolya91
0
1 вариант
1
а)...=3b
б)...=(7ху²)/(28x²y²)=1/(4x)
в)...=((m+n)(m-n)(m+n))/(5(m-n)(m+2n))=(m+n)/5
г)...=((х-1)(х-1)·х·(х+5))/((x-5)(x+5)(x-1))=(x(x-1))/(x-5)

2
а)...=((х-у)²(4ху+4х(х-у)))/(4x²y(x-y))=((x-y)²·4x²)/(4x²y(x-y))=(x-y)/y
б)...=((x²-3x-5x+16)/(x-3)):((3x²-9x-3x)/(x-3))=(x²-8x+16)/(3x²-12x)=(x-4)²/(3x(x-4))=(x-4)/(3x)

3
а)(1-8х)/(3x)=0
ОДЗ х≠0
1-8х=0
х=1/8

б)(2х²-4)/(5-x)=-2x
ОДЗ x≠5
2x²-4=-10x+2x²
10x=4
x=2/5

в)(х+3)/x=(x+10)/(x-3)
ОДЗ х≠3   х≠0
х²-9=х²+10х
10х=-9
х=-9/10

2 вариант
1
а)...=4а
б)...=(21х³у·3)/(7x³y²)=9/y
в)...=((m-3n)(m-n)(m+n))/((m+n)·3·(m-3n))=(m-n)/3
г)...=((х-4)(х+4)(х+2))/((x+2)²·x·(x-4))=(x+4)/(x(x+2))

2
a)...=((9y(x+y)-9xy)·(x+y)²)/(x(x+y)·9y²)=(9y²(x+y)²)/(x(x+y)·9y²)=(x+y)/x
б)...=((4х²-8х-12х)/(x-2)):((x²-2x-8x+25)/(x-2))=(4x²-20x)/(x²-10x+25)=
(4x(x-5))/(x-5)²=4x/(x-5)

3
a)(3x+1)/(6x)=0
ОДЗ: х ≠0
3х+1=0
х=-1/3

б)(5-4х²)/(x-3)=-4x
ОДЗ  x≠3
(5-4x²)=-4x(x-3)
5-4x²=-4x²+12x
x=5/12

в)(х-2)/x=(x+20)/(x+2)
ОДЗ   х≠0   х≠-2
х(х+20)=х²-4
х²+20х=х²-4
20х=-4
х=-1/5
Похожие вопросы